The Implication of Reactive Oxygen Species and Antioxidants in Knee Osteoarthritis - Tudorachi, Nicoleta Bianca; Totu, Eugenia Eftimie; Fifere, Adrian; Ardeleanu, Valeriu; Mocanu, Veronica; Mircea, Cornelia; Isildak, Ibrahim; Smilkov, Katarina; Carausu, Elena Mihaela (MDPI, 2021)
Knee osteoarthritis (KOA) is a chronic multifactorial pathology and a current and essential challenge for public health, with a negative impact on the geriatric patient's quality of life. The pathophysiology is not fully known; therefore, no specific treatment has been found to date. The increase in the number of newly diagnosed cases of KOA is worrying, and it is essential to reduce the risk factors and detect those with a protective role in this context. The destructive effects of free radicals consist of the acceleration of chondrosenescence and apoptosis. Among other risk factors, the influence of redox imbalance on the homeostasis of the osteoarticular system is highlighted. The evolution of KOA can be correlated with oxidative stress markers or antioxidant status. These factors reveal the importance of maintaining a redox balance for the joints and the whole body's health, emphasizing the importance of an individualized therapeutic approach based on antioxidant effects. This paper aims to present an updated picture of the implications of reactive oxygen species (ROS) in KOA from pathophysiological and biochemical perspectives, focusing on antioxidant systems that could establish the premises for appropriate treatment to restore the redox balance and improve the condition of patients with KOA.
Keywords: oxidative stress; ROS; antioxidants; pathophysiology; KOA; cellular senescence; apoptosis; COLLAGEN-INDUCED ARTHRITIS; INDUCED LIPID-PEROXIDATION; NECROSIS-FACTOR-ALPHA; NF-KAPPA-B; NITRIC-OXIDE; TEA CATECHINS; HUMAN PLASMA; DNA-DAMAGE; VITAMIN-C; Biochemistry & Molecular Biology; Pharmacology & Pharmacy; Food Science & Technology